Social and Cultural Dynamics and Bureaucratic Challenges in the Implementation of Rural Policies - Wirata, Gede; Djaja, Djuniawan Karna; Handayani, Tri Quari; Widjaja, Yosua Giovanni; Yusup, Aldian (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Rural development policy plays a strategic role in reducing social inequality and strengthening local economic structures. However, its implementation often faces bureaucratic constraints and complex socio-cultural dynamics. This study aims to analyze how socio-cultural dynamics influence bureaucratic performance and the effectiveness of rural policy implementation, as well as to identify the challenges bureaucracies face in adapting to local social changes. The research employed a qualitative literature review method through systematic analysis of academic journals, research reports, and policy documents. Data were analyzed thematically to identify relationships between cultural values, social structures, and bureaucratic effectiveness. The findings reveal that the success of rural policy implementation is highly dependent on the bureaucracy’s ability to adapt to local values, foster community participation, and apply adaptive governance principles. Responsive and culturally sensitive bureaucracies tend to achieve greater social legitimacy, strengthen public trust, and accelerate the attainment of rural development goals.